Application of carbon dioxide for heavy oil enhanced oil recovery via vapour extraction process [electronic resource] - Mehrdad Hokmabadi, 1980-, author (2013)
Thesis (Sarjana Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2013